Digital Storytelling And Interactive E-Books: Fostering Young Adult Learners’ Reading Engagement And Vocabulary Acquisition - Fovi Sriyuliawati; Rika Septiani; Rinaepi Rinaepi (Community Engagement and Emergence Journal (CEEJ), 2026)
This article synthesizes contemporary research on the integration of digital storytelling and interactive e-books in secondary and higher education, with particular attention to their contribution to young adult learners’ reading engagement and vocabulary acquisition. Using a systematic literature review approach guided by PRISMA 2020, the study examines empirical research on interactive digital texts, multimodal glosses, audio-supported reading, branching narratives, and learner-generated digital stories. The analysis is informed by Paivio’s Dual Coding Theory, Mayer’s Cognitive Theory of Multimedia Learning, and Sweller’s Cognitive Load Theory. The findings indicate that well-designed interactive digital texts generally support receptive vocabulary learning, lexical retention, reading motivation, and active participation by combining verbal, visual, and auditory information. However, productive vocabulary mastery and higher-order reading comprehension require more than exposure to multimedia input. Their development depends on meaningful vocabulary retrieval, communicative production, teacher scaffolding, peer interaction, and structured opportunities for reflection. The review also shows that decorative animations, unrelated sound effects, excessive hyperlinks, and poorly positioned interactive features may increase extraneous cognitive load and encourage fragmented or superficial reading. Therefore, the effectiveness of digital storytelling and interactive e-books is determined by feature congruence, cognitive-load management, learner control, accessibility, and pedagogical mediation. When integrated into task-based, collaborative, and participatory learning environments, these technologies can move young adult learners from passive digital-text consumption toward active interpretation, productive language use, and multimodal meaning-making.